Closed-loop experimental investigation of single-phase natural circulation flow phenomena based on temperature and heating power variations. (February 2021) - Bello, Solomon; Gao, Puzhen; Lin, Yuqi
Highlights: Experiment has been carried out to study flow phenomena in a natural circulation system. A closed rectangular natural circulation loop with single heated channel has been investigated. The Effects of Temperature and Heating Power variations at low system pressure on flow characteristics are presented. Single-phase flow behaviors are observed and critically analyzed. Abstract: Experimental investigation of single-phase, low pressure natural circulation flow phenomena has been carried out. The study aims to critically analyze the thermal hydraulic parameters (temperature and heating power) variations as it affects transfer of heat in a closed-loop rectangular natura l circulation facility having a single heated channel at predetermined inlet sub cooled temperature varied from 40 to 80 °C. Heating power varies between 7 kW−13 kW to portray several conditions of the reactor power in response to temperature changes while sustaining single-phase flow circulation through the hydraulic loop. Real-time signals of thermal hydraulic responses are observed via a graphical interface for data acquisition when stable flow or self-sustained flow oscillations are achieved. Results obtained were analyzed at several sections of the hydraulic circuit which are basically pressure drops and flow rate due to temperature differences and heating power increments. These results and observations made through them thus contribute to the database which is important for characterizing natural circulation phenomena and acquisition of dominants parameters for the scaling analysis of future designs.